Relationship between pole vault biomechanics and previous injuries - Edouard, P.; Sanchez, H.; Bourrilhon, C.; Homo, S.; Frère, J.; Cassirame, J. (British Journal of Sports Medicine, 2021)
Background During pole vault, a high level of energy is transferred from horizontal speed of athlete to the pole. Several ways of performing the pole vault exist, and could be associated with specific injury risk.